Approaches and Techniques of Phenomenon-Based Learning: PheBL - Jongyung, Thanee (Journal of Education and Learning Reviews, 2025)
Background and Aims: Phenomenon-Based Learning is important because it connects academic content to real-world issues, making learning more meaningful and engaging for students. It improves critical thinking and prepares students to face real-world challenges by addressing complex, multifaceted problems from multiple perspectives. This paper aims to investigate the approaches and techniques of phenomenon-based learning. PheBL Methodology: The paper presents a thorough examination of various educational approaches and techniques within the PheBL framework. It systematically investigates how integrating real-world phenomena from multiple disciplines can improve teaching practices and student learning outcomes. Results: The finding found that Phenomenon-Based Learning (PheBL) is a comprehensive approach to education that places real-world phenomena at the center of inquiry and learning. By combining disciplines around a common phenomenon, PheBL encourages students to investigate complex, multifaceted issues from multiple perspectives. This methodology encourages deeper comprehension and critical thinking by actively involving students in problem-solving and inquiry. Finally, PheBL’s approach not only aligns educational practices with real-world contexts but also increases student engagement and comprehension by employing an interdisciplinary lens that reflects the world’s interconnectedness. Conclusion: The findings show that Phenomenon-Based Learning (PheBL) effectively centers education on real-world issues, bringing together multiple disciplines to foster a deeper, more critical understanding of complex topics. This approach improves student engagement and comprehension while also aligning learning practices with the interconnected nature of real-world problems.